A CONCEPTUAL MODEL OF BUSINESS MODEL TRANSFORMATION FOR DAY-OLD CHICK (DOC) TRANSPORTATION - Syamsul Ma'Arif,; Dikky Indrawan,; Faridatut Rahmawati, (Journal of Islamic, Social, Economics and Development, 2022)
This digital era 4.0 has led the company's innovation not only the products andservices area, but also in an efficient and competitive logistics system in a digital environment.Logistics systems are concerned with the flow and storage of goods and related information.The increasing demands and changes of the external environment encourage companies tomake transformational changes, especially in their business models. Changes of business modelrequire a full economic evaluation, which are measured both of costs (inputs) and benefits(outputs) logistics. PT Mega Satwa Perkasa is a chicken hatchery company that delivers DOCtransportation to third parties expedition. This study aims to analyze cost effectiveness fromDOC logistics activities and to analyze alternative business model scenarios on the DOClogistics activities of PT Mega Satwa Perkasa. This research used business model canvas(BMC), business scenario analysis and cost effectiveness analysis to perform the study. Thisresearch is very broad development possibilities in the scope of business scenarios so that itcan be modeled and evaluated by scientific points of view.